Efficiency-Adjusted Public Capital and Growth - Gupta, Sanjeev (IMF Working Papers; Working Paper, 2011)
This paper constructs an efficiency-adjusted public capital stock series and re-examines the public capital and growth relationship for 52 developing countries. The results show that public capital is a significant contributor to economic growth. Although the estimated coefficient for the income share of public capital is larger in middle- than in low-income countries, the opposite is true for the marginal product of public capital. The quality of public investment, as measured by variables capturing the adequacy of project selection and implementation, are statistically significant in explaining variations in economic growth, a result mainly driven by low-income countries.